الصلابة النفسية و علاقتها بأساليب مواجهة الضغوط لدى عينة من الممرضين - شعيب نور الايمان; بوكريكرة سارة تاتلاس; فطام جمال الدين (My University, 2023)
The current study aimed to study the issue of the relationship between psychological hardiness and stress coping methods among a sample of nurses; by trying to identify the differences between the sexes in both the level of psychological hardness and coping strategies for stress among the study sample. As well as revealing the existence of a relationship between psychological hardness and strategies for coping with stress among the study sample. The study was based on a sample of (35) nurses of both sexes, who were chosen randomly in the mixed hospital “Ali Bin Daghin” 240 beds. To collect data, relying on the descriptive analytical method Scale: Game Boys (Santa Clara, University of California, translated by Ahmed Abu Saad, 2007) Researcher scale: Hedaya Samih Ahmed, University of Gaza, 2010) After unpacking and analyzing the obtained results, the following results were reached: There is a relationship between stress coping strategies and psychological hardness among the study sample There are differences between the sexes in the level of psychological hardness among the study sample. There are differences between the sexes in the level of stress coping strategies Keywords: psychological toughness, stress coping strategies, nurse.